THE MEDIATING EFFECT OF SOCIAL EFFICACY ON THE RELATIONSHIP BETWEEN SOCIAL SUPPORT AND NETWORK DEPENDENCE AMONG COLLEGE STUDENTS - Lan, Qiandong; Gao, Yimin (Chinese Journal of Social Science and Management, 2025)
In the information age, internet penetration is increasing day by day, and college students have become one of the groups with the highest rates of internet usage. They use the internet to search for information, browse content, send and receive emails, chat and make friends, play games, and watch live broadcasts. The internet has become an integral part of their academic and daily lives. However, while the internet brings significant convenience to college students, it also leads many to develop dependence or even addiction. This issue not only negatively aﬀects their physical and mental development but also presents a practical management challenge for universities and the broader educational system. Drawing on a review of relevant domestic and international research, this study conducted empirical research using a questionnaire survey and statistical analysis. Using college students at H University as the sample, a total of 502 valid responses were collected. Regression and mediation analyses were employed to test the theoretical hypothesis that social support negatively aﬀects internet dependence, and that social efficacy mediates the relationship between social support and internet dependence. As a result, a mediating model was established, linking college students’ social support, social efficacy, and internet dependence. Based on this, the study oﬀers suggestions from the perspectives of family, schools, society, and students themselves to help reduce internet dependence and foster a healthy and balanced approach to internet use.